Does MPV / Plt ratios support the diagnosis in acute ischemic stroke patients? - Sahin Tutak, Ayse (Annals of Medical Research, 2021)
None
Keywords: Acute Ischemic Stroke; Mean Platelet Volume; Platelet Count; Mean Platelet Volume-To- Platelet Ratio.